In situ and ex situ diversity analysis of priority crop wild relatives in Norway. Issue 11 (24th August 2016) - Phillips, Jade; Asdal, Åsmund; Magos Brehm, Joana; Rasmussen, Morten; Maxted, Nigel
Abstract: Aim: To contribute directly to Norway's national and international commitments to systematic, long‐term conservation of crop wild relatives (CWR) by ensuring both the in situ and ex situ protection and availability of a broad range of CWR genetic diversity within the country. Location: Norway. Methods: We created a priority list of CWR within Norway based upon four main criteria including economic value from national to global level of associated crops and inclusion in Annex 1 of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA). Species presence data were gathered from the Global Biodiversity Information Facility (GBIF) and used for predictive species distribution modelling in MaxEnt.capfitogen software was utilized to create an ecogeographic land characterization (ELC) map and to identify complementary in situ genetic reserves and ex situ collecting priorities which target the full range of ecogeographic diversity of taxa. Results: An inventory of 204 priority CWR within Norway was compiled. A grid cell complementary network of 19 in situ areas (~10 km 2 ) conserved 201 priority CWR, and a separate analysis identified a protected area complementary network of 23 reserves that conserved 181 priority taxa. For ex situ conservation, 177 taxa did not have ex situ accessions and of the 24 with accessions, 15 had the minimum of five populations conserved throughout their ecogeographic range. Main conclusions: We present the first comprehensive national recommendations for in situ and ex situ conservation of 204 priority CWR in Norway. Proposals target the conservation of the ecogeographic diversity of the priority CWR and hence their genetic diversity. Both the priority taxa and the methodology used are applicable at regional and global scales with the recommendations not only helping Norway to meet its international obligations for conservation of genetic diversity of CWR but also ensuring this genetic diversity is available for use in tackling global food security.